Maternal death surveillance efforts: notification and review coverage rates in 30 low-income and middle-income countries, 2015–2019 - Jason Hsia; Michel Brun; Jean-Pierre Monet; Florina Serbanescu; Lillian Whiting-Collins; A C Moran (BMJ Open)
Objective Performance of maternal death surveillance and response (MDSR) relies on the system’s ability to identify and notify all maternal deaths and its ability to review all maternal deaths by a committee. Unified definitions for indicators to assess these functions are lacking. We aim to estimate notification and review coverage rates in 30 countries between 2015 and 2019 using standardised definitions.Design Repeat cross-sectional surveys provided the numerators for the coverage indicators; United Nations (UN)-modelled expected country maternal deaths provided the denominators.Setting 30 low-income and middle-income countries responding to the Maternal Health Thematic Fund annual surveys conducted by the UN Population Fund between 2015 and 2019.Outcome measures Notification coverage rate (CRn) was calculated as the proportion of expected maternal deaths that were notified at the national level annually; review coverage rate (CRr) was calculated as the proportion of expected maternal deaths that were reviewed annually.Results The average annual CRn for all countries increased from 17% in 2015 to 28% in 2019; the average annual CRr increased from 8% to 13%. Between 2015 and 2019, 22 countries (73%) reported increases in the CRn—with an average increase of 20 (SD 18) percentage points—and 24 countries (80%) reported increases in CRr by 7 (SD 11) percentage points. Low values of CRr contrasts with country-published review rates, ranging from 46% to 51%.Conclusion MDSR systems that count and review all maternal deaths can deliver real-time information that could prompt immediate actions and may improve maternal health. Consistent and systematic documentation of MDSR efforts may improve national and global monitoring. Assessing the notification and review functions using coverage indicators is feasible, not affected by fluctuations in data completeness and reporting, and can objectively capture progress.